2008
DOI: 10.1021/la802991g
|View full text |Cite
|
Sign up to set email alerts
|

Wrapping of Self-Organized Fluorescent Nanofibers with a Silica Wall

Abstract: Amphiphilic compounds 1 and 2, composed of an aromatic pyrene core and an amphiphilic three-branched unit, were synthesized and investigated for their self-organizing process in solution by UV-vis, fluorescence spectra, Fourier transform infrared (FT-IR), X-ray diffraction (XRD), and fluorescence microscopes. While 2 formed spherical objects in a mixed solvent of methanol and water, 1 assembled into long, flexible, and fluorescent fibers through pi-pi stacking of pyrene cores and hydrogen bonding among amide g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…It has been reported that the pyrene excimer emission band depends on the conformation of the excimer: the sandwich type excimer shows an emission band at 460 nm, and the band at 416 nm is ascribed to the partial overlap type excimer. [37][38][39][40] Here, the pyrene moiety in the PyC0 gels formed an excimer with a partial overlap as a result of pyrene being linked to glutamide directly. In the self-assemblies of the gels, an intermolecular hydrogen-bonding array of the glutamide moieties disturbed the formation of excimer structures.…”
Section: Fluorescence Properties Of the Gelsmentioning
confidence: 99%
“…It has been reported that the pyrene excimer emission band depends on the conformation of the excimer: the sandwich type excimer shows an emission band at 460 nm, and the band at 416 nm is ascribed to the partial overlap type excimer. [37][38][39][40] Here, the pyrene moiety in the PyC0 gels formed an excimer with a partial overlap as a result of pyrene being linked to glutamide directly. In the self-assemblies of the gels, an intermolecular hydrogen-bonding array of the glutamide moieties disturbed the formation of excimer structures.…”
Section: Fluorescence Properties Of the Gelsmentioning
confidence: 99%
“…4). Amphiphilic compounds that self-organize into fluorescent nanofibers can be obtained by branching, for example, three poly(ether) segments to a pyrene core (12) (Kimura et al, 2009). In the T-shaped aromatic amphiphiles based on oligo(ethylene oxide) dendrons (13), the aromatic segments are stacked with dimeric association to maximize π−π interactions.…”
Section: Nanofibers Made Of Low-molecular-weight Molecules With Appenmentioning
confidence: 99%
“…It is noteworthy that the fibers made of 12 were subsequently wrapped with an ultrathin silica wall, using a sol-gel process. The resulting fibers can then be considered as electronic cables that are composed of a conductive organic core and an insulating inorganic layer (Kimura et al, 2009). …”
Section: Nanofibers Made Of Low-molecular-weight Molecules With Appenmentioning
confidence: 99%
“…25,26 For example, Chen et al 26 have obtained the organogels of SWNTs with ferrocene-grafted poly (p-phenyleneethynylene)s through non-covalent interactions. Considering pyrene is the most popular species for non-covalent attachment with CNT through p-p stacking, [27][28][29] in this paper, we designed a new low molecular gelator bearing a pyrene group and fabricated organogels with pristine SWNTs through mixing with LPG.…”
Section: Introductionmentioning
confidence: 99%